INOVASI STRATEGI PENDIDIKAN UNTUK MENINGKATKAN PEMBELAJARAN ANAK BERKEBUTUHAN KHUSUS - Ashrul Rezky Siagian; Rahmat Syaleh (Yayasan Baitul Hikmah al-Zain, 2025)
Children with special needs (CWSN) require educational approaches tailored to their individual characteristics and needs. The main problems in educating CWSN include the lack of appropriate teaching strategies, limited facilities, and insufficient teacher competencies in handling diverse abilities. This study aims to identify and analyze effective educational strategies for CWSN in inclusive school settings. The research uses a qualitative descriptive method with a case study approach conducted at an inclusive school in Indonesia. Data were collected through observations, interviews with teachers, and learning documentation. The results indicate that effective educational strategies for CWSN include individualized learning plans, multisensory-based learning, collaboration between teachers and support staff, and active parental involvement. The conclusion is that the success of education for CWSN depends largely on flexible methods, teacher competence, and a supportive adaptive learning environment. Therefore, developing inclusive and child-centered learning strategies is key to achieving equitable and quality education for all children